Pemodelan Nilai TQI Berbasis Ketebalan Ballast dan Parameter Geometri pada Jalur Rel 1435 mm - Mochammad Choirusydhia Pratama; Nugroho Utomo; Achmad Dzulfiqar Alfiansyah (Universitas Batanghari Jambi, 2026)
The Track Quality Index (TQI) is an essential indicator for evaluating the geometric quality of railway tracks. This study aims to analyze TQI values and predict their degradation based on geometric parameters and ballast thickness on the Makassar–Parepare railway line with a 1435 mm track gauge. The data used include track recording car measurements, ballast thickness, as well as traffic load and frequency. The analytical method employed is simple linear regression to determine the effect of ballast thickness on TQI. The results show that 66.66% of the track segments fall into the “Excellent” category. Furthermore, ballast thickness has a significant influence, with an R² value of 0.973, indicating that the thicker the ballast layer, the better the track quality. Long-term TQI prediction reveals an increase in TQI values over time due to ballast degradation, with the average value rising from 24.23 in the 5th year to 69.61 in the 25th year. These findings highlight the importance of periodic maintenance interventions based on TQI prediction to sustain the safety and comfort of railway operations.